Pharmacological Activities of Psoralidin: A Comprehensive Review of the Molecular Mechanisms of Action - Sharifi-Rad, Javad; Kamiloglu, Senem; Yeskaliyeva, Balakyz; Beyatli, Ahmet; Alfred, Mary Angelia; Salehi, Bahare; Calina, Daniela; Docea, Anca Oana; Imran, Muhammad; Anil Kumar, Nanjangud Venaktesh; Romero-Román, Maria Eugenia; Maroyi, Alfred; et al. (Frontiers in Pharmacology, 2020)
Compilating the most relevant studies of psoralidin, a coumarin from seeds of Cullen corylifolium (L.) Medik. (syn. Psoralea corylifolia L.), has recently confirmed this compound display interesting pharmacological properties. Last years, interest in this compound had been changed and take it up due to its widespread beneficial for estrogen-related diseases and as a chemopreventive agent. A growing number of preclinical evidence indicate that psoralidin has anticancer, antiosteoporotic, anti-inflammatory, anti-vitiligo, antibacterial, antiviral and antidepressant-like effects. Here, we provide a comprehensive and critical review of psoralidin on its bioavailability, pharmacological activities with underlying the molecular mechanisms and cell signaling pathways. In the light of these beneficial actions for human health of psoralidin, this paper gathers complete information on its pharmacotherapeutic effects and opens new natural therapeutic perspectives in chronic diseases.